INFLUENCE OF FOOD QUALITY OF CAFE IN MEDAN TOWARDS THE CUSTOMER SATISFACTION - Daniel Cassa Augustinus; Donna Iona (Universitas Pelita Harapan Medan Campus, 2020)
Survey is conducted to understand how perception of food quality by its customers of City Ice Cream Cafe in Medan Fair Plaza influence their satisfaction. This research used primary and secondary data in order to obtain information needed. The result of coefficient of determination (R2) is 0.225. It means that the 77.5% of customer satisfaction is influenced by food quality and the remaining 22.5% is influenced by other variables besides this research. The result of t-test hypothesis indicates that t-count value obtained is 4.844 that will be compared with t-table in amount of 1.664. T-count (4.844) is greater than the value of t-table (1.664). Therefore, hypothesis alternative (H1) is accepted that there is a significant relationship between food quality and customer satisfaction at City Ice Cream Cafe Medan Fair. As the recommendation, restaurant should pay more attention on its food quality in order to improve the restaurant.Keywords: Food Quality, Customer Satisfaction, and City Ice Cream Cafe Medan Fair